THE USE OF MOBILE-ASSISTED LANGUAGE LEARNING APPLICATION IN PRONUNCIATION TRAINING - Fatimah, Siti (Universitas Gunadarma, 2021)
Pronunciation is one of the most important things to master when it comes to Second Language Acquisition (SLA). Nowadays, mobile-assisted language learning (MALL) applications have been emerging. Learners can practice at the reach of their fingertips through the use of their own mobile devices. This study aims to investigate whether the existing mobile-assisted language learning application (ELSA Speak) is effective to help EFL learners train and improve their pronunciations. This study also seeks to know the most difficult sounds to pronounce by Indonesian EFL learners and highlights learners’ thoughts on the application itself including the ease of use, the clarity of pronunciation models by native speakers, as well as the strength and weaknesses of the application. 15 EFL learner participants were involved in this study. They were asked to do a pretest before using the application. The participants then practiced their pronunciation on their own using this application for a week. A post-test was conducted to know their pronunciation progress. They were also given a questionnaire to examine their perceptions of the application. The results show that the mobile-assisted language learning application ELSA speak is quite effective to help learners train and improve their pronunciation. This application is also easily operated and has a lot of features that help learners train their pronunciation easily. Thus, it supports distance language education (DLE). The most difficult English sounds to pronounce according to the participants are Ɵ, t, f, v, tʃ, e, æ, ð, and d, with Ɵ and t as the majority. Lastly, despite being considered as a helpful and convenient pronunciation training application, some things need to be improved, such as the need for Indonesian translation on the words provided to enrich learners’ vocabulary at the same time.Keywords: Pronunciation, Pronunciation Training App,